Wpływ poziomu zakłóceń losowych na możliwość identyfikacji modeli ARIMA dla niestacjonarnych szeregów czasowych - Nazarko, Joanicjusz; Rybaczuk, Mikołaj; Jurczuk, Arkadiusz (Influence of random noise on an identification of ARIMA models for non-stationary processes, 2006)
According to Box-Jenkins’ methodology a key issue in time-series modeling with ARIMA models is to identify proper class and their order. The basis for the identifying is an analysis of plot of autocorrelation (ACF) and partial correlation functions (PACF). The paper presents results of the second part of a simulation research on influence of white noise presence and its variance level on identification of ARIMA models for three types of non-stationary processes: ARIMA( 1,1,0), ARIMA(0,110) and ARIMA( 1,1,1). The effect of noise variance level on a quality of estimation of ARIMA models has been also presented in the paper. It has been considered that possibility of correct identification and estimation strongly depends on presence and variance of a random noise.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (13); 2006; nr 1126, s. 175-185